The effect of reframing technique on self-awareness on learning of the 7th grade students - Andi Zulfiana; Farida Aryani; Muhammad Jufri (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study is aimed (1) to describe the self-awareness on learning of the 7th grade students, (2) to describe the implementation of technique reframing in affecting the self-awareness on learning of the 7th grade students, and (3) to investigate the effect of reframing technique on self-awarenss on learning of the 7th grade students. Quantitative approach was used in this study by implementing quasi experimental design and using Pretest-Posttest Control Group Design to 24 samples. Data collection techniques applied in this research were self-awareness scale on learning developed by the researcher, observation, and interview. Data analysis technique applied in tis study was independent samples t-test which was conducted through Statistical Product for Service Solustion (SPSS) version 24.0. The study found that (1) the self-awareness on learning of the 7th grade students before the treatment of reframing technique was in low category, while that after the treatment of such technique was in moderate and high categories, (2) the self-awareness on learning of the 7th grade students was increased after the treatment of reframing technique, and (3) reframing technique can increase the self awareness on learning of the 7th grade students.